Ethosomes and Transethosomes for Mangiferin Transdermal Delivery - Maddalena Sguizzato; Francesca Ferrara; Supandeep Singh Hallan; Anna Baldisserotto; Markus Drechsler; Manuela Malatesta; Manuela Costanzo; Rita Cortesi; Carmelo Puglia; Giuseppe Valacchi; Elisabetta Esposito (MDPI AG, 2021)
Mangiferin is a natural glucosyl xanthone with antioxidant and anti-inflammatory activity, making it suitable for protection against cutaneous diseases. In this study ethosomes and transethosomes were designed as topical delivery systems for mangiferin. A preformulation study was conducted using different surfactants in association with phosphatidylcholine. Vesicle dimensional distribution was monitored by photon correlation spectroscopy, while antioxidant capacity and cytotoxicity were respectively assessed by free radical scavenging analysis and MTT on HaCaT keratinocytes. Selected nanosystems were further investigated by cryogenic transmission electron microscopy, while mangiferin entrapment capacity was evaluated by ultracentrifugation and HPLC. The diffusion kinetics of mangiferin from ethosomes and transethosomes evaluated by Franz cell was faster in the case of transethosomes. The suitability of mangiferin-containing nanovesicles in the treatment of skin disorders related to pollutants was investigated, evaluating, in vitro, the antioxidant and anti-inflammatory effect of ethosomes and transethosomes on human keratinocytes exposed to cigarette smoke as an oxidative and inflammatory challenger. The ability to induce an antioxidant response (HO-1) and anti-inflammatory status (IL-6 and NF-kB) was determined by RT-PCR and immunofluorescence. The data demonstrated the effectiveness of mangiferin loaded in nanosystems to protect cells from damage. Finally, to gain insight into the keratinocytes' uptake of ethosome and transethosome, transmission electron microscopy analyses were conducted, showing that both nanosystems were able to pass intact within the cells.